COVID-19 Severity Is Associated with Differential Antibody Fc-Mediated Innate Immune Functions - Adeniji, Opeyemi S.; Giron, Leila B.; Purwar, Mansi; Zilberstein, Netanel F.; Kulkarni, Abhijeet J.; Shaikh, Maliha W.; Balk, Robert A.; Moy, James N.; Forsyth, Christopher B.; Liu, Qin; Dweep, Harsh; Kossenkov, Andrew; et al. (mBio, 2021)
A state of hyperinflammation and increased complement activation has been associated with coronavirus disease 2019 (COVID-19) severity. However, the pathophysiological mechanisms that contribute to this phenomenon remain mostly unknown. Beyond neutralization, antibodies binding to their Fc receptors elicit several innate immune functions including antibody-dependent complement deposition (ADCD), antibody-dependent cell-mediated phagocytosis (ADCP), and antibody-dependent cell-mediated cytotoxicity (ADCC). These functions are beneficial, as they contribute to pathogen clearance; however, they also can induce inflammation. We tested the possibility that qualitative differences in SARS-CoV-2-specific antibody-mediated innate immune functions contribute to coronavirus disease 2019 (COVID-19) severity. We found that anti-S1 and anti-RBD antibodies from hospitalized COVID-19 patients elicited higher ADCD but lower ADCP compared to antibodies from nonhospitalized COVID-19 patients. Consistently, higher ADCD was associated with higher systemic inflammation, whereas higher ADCP was associated with lower systemic inflammation during COVID-19. Our study points to qualitative, differential features of anti-SARS-CoV-2 specific antibodies as potential contributors to COVID-19 severity. Understanding these qualitative features of natural and vaccine-induced antibodies will be important in achieving optimal efficacy and safety of SARS-CoV-2 vaccines and/or COVID-19 therapeutics. IMPORTANCE A state of hyperinflammation and increased complement activation has been associated with coronavirus disease 2019 (COVID-19) severity. However, the pathophysiological mechanisms that contribute to this phenomenon remain mostly unknown. Our data point to a qualitative, rather than quantitative, difference in SARS-CoV-2-specific antibodies’ ability to elicit Fc-mediated innate immune functions as a potential contributor to COVID-19 severity and associated inflammation. These data highlight the need for further studies to understand these qualitative features and their potential contribution to COVID-19 severity. This understanding could be essential to develop antibody-based COVID-19 therapeutics and SARS-CoV-2 vaccines with an optimal balance between efficacy and safety.